ASP.NET MVC database applications performance - Borys, Paweł; Pańczyk, Beata (Journal of Computer Sciences Institute, 2018)
During web application development, working with a database and choosing appropriate tool for database managing is extremely important. This choice influences both final application and its development process. However there is a large number of possibilities of choosing the best tool to use in a project. It often provides some difficulties. The main goal of this paper is to present the advantages and disadvantages of three popular solutions for ASP.NET MVC platform (ADO.NET, Entity Framework, NHibernate) to help make the proper decision.